Implementation of Storyling Methods Using Hands to Stimulate Early Children's Language Development in RA At-Taqwa Cirebon City - Rika Rohmatul Fawaiz; Jajang Aisyul Muzakki; Masdudi Masdudi (Ilmu Inovasi Nusantara, 2022)
This research is motivated by the importance of stimulating language development, which is the most complex characteristic of human abilities. Language development can be instilled in various methods, one of which is the storytelling method. The storytelling method can be used as an appropriate method in stimulating early childhood language development. The storytelling method using hand puppets makes children interested and can stimulate language development. This type of research is descriptive qualitative. The main subjects in this study were the principal and teacher of RA At-Taqwa Cirebon City. Data collection techniques used are interviews, observation, and documentation. Data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the storytelling method using hand puppets in stimulating early childhood language development is implemented and listed in the curriculum and STTPA. The implementation of the storytelling method using hand puppets in stimulating early childhood language development is able to stimulate language development through storytelling using hand puppets which is done during learning. Children respond to what the teacher tells, children are able to retell with more vocabulary, children are able to express feelings of pleasure and ask a lot of characters told in simple sentences. The implementation of learning RA At-Taqwa has implemented the storytelling method using hand puppets with steps of planning, implementation, storytelling techniques and evaluation of storytelling. The supporting factors for the storytelling method using hand puppets in stimulating early childhood language development are hand puppet media and competent teachers. The inhibiting factors are active children and different abilities of children